Presence on idiotype-specific suppressor T cells of receptors that interact with molecules bearing the idiotype (The Rockefeller University Press, 1977)
All A/J mice produce anti-p-azophenylarsonate (anti-Ar) antibodies, some of which share a cross-reactive idiotype. The idiotype can be suppressed by treatment with anti-idiotypic antiserum before immunization, although normal concentrations of anti-Ar antibodies are synthesized. We have previously reported that such suppressed mice, if hyperimmunized and then allowed to rest, contain up to 10% of splenic T cells which form rosettes with autologous RBC coated with Fab fragments of anti-Ar antibodies bearing the idiotype. Our present results indicate that the rosette-forming T cells include the idiotype-specific suppressor T-cell population. The suppressive activity is largely depleted by removal of the rosette-forming lymphocytes, and the rosettes themselves are highly suppressive. The data do not establish whether all of the idiotype-specific rosette-forming cells are suppressor cells. The system may provide a source of large numbers of suppressor cells for further study, and facilitate investigation of the mechanism of generation of idiotype-specific suppressor cells.